Acculturation, Enculturation, and Symptoms of Depression in Hispanic Youth: The Roles of Gender, Hispanic Cultural Values, and Family Functioning - Lorenzo-Blanco, Elma I. (J Youth Adolesc, 2012)
The risk for depression increases as Hispanic youth acculturate to U.S. society. This association is stronger for Hispanic girls than boys. To better understand the influence of culture and family on depressive symptoms, we tested a process-oriented model of acculturation, cultural values, and family functioning. The data came from Project RED, which included 1,922 Hispanic students (53 % girls; 86 % were 14 years old; and 84 % were U.S. born) from Southern California. We used data from 9th to 11th grade to test the influence of acculturation-related experiences on depressive symptoms over time. Multi-group structural equation analysis suggested that both family conflict and cohesion were linked with depressive symptoms. Hispanic cultural values were associated with family cohesion and conflict but the strength and direction of these relationships varied across cultural values and gender. For girls and boys, familismo and respeto were associated with higher family cohesion and lower family conflict. Moreover, gender roles were linked with higher family cohesion in girls but not in boys. These results indicate that improving family functioning will be beneficial for boys’ and girls’ psychological well-being. This may be achieved by promoting familismo and respeto for boys and girls and by promoting traditional gender roles for girls.